1996
DOI: 10.1108/02651339610111353
|View full text |Cite
|
Sign up to set email alerts
|

Competitive environmental scanning and export involvement: an initial inquiry

Abstract: Presents an initial inquiry into the role of competitive environmental scanning in the internationalization process. Explores specifically the relationship between dimensions of competitive environmental scanning and measures of export market involvement and success. Finds that the results provide strong support for the contention that scanning capabilities must be developed for firms to pursue strategies that will result in a higher degree of export involvement and export success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 58 publications
(68 reference statements)
1
26
1
Order By: Relevance
“…Based on a survey conducted with 438 firms in the USA Lim et al also obtained a positive relationship between changes in products and export success (measured by the export intensity). With regard to technological, economic and socio-political changes, the relationship was not found to be statistically significant (Lim et al, 1996). Also with regard to the instability of the industry, Gao et al (2010), using a sample of 18,644 firms in China, with data gathered over a four-year period (2002)(2003)(2004)(2005), also concluded that the relationship between the instability of the industry (measured by the sum of the fluctuations of the market shares of each firm in a specific industry) and export intensity was not statistically significant.…”
Section: The Impact Of Industry Characteristics On Export Intensitycontrasting
confidence: 51%
“…Based on a survey conducted with 438 firms in the USA Lim et al also obtained a positive relationship between changes in products and export success (measured by the export intensity). With regard to technological, economic and socio-political changes, the relationship was not found to be statistically significant (Lim et al, 1996). Also with regard to the instability of the industry, Gao et al (2010), using a sample of 18,644 firms in China, with data gathered over a four-year period (2002)(2003)(2004)(2005), also concluded that the relationship between the instability of the industry (measured by the sum of the fluctuations of the market shares of each firm in a specific industry) and export intensity was not statistically significant.…”
Section: The Impact Of Industry Characteristics On Export Intensitycontrasting
confidence: 51%
“…Moreover, these facets allow the firm to know what the tastes, preferences and habits of foreign consumers are with respect to the product exported, and also those of its competitors. This matter facilitates the design of strategies which provide the firm with a sustainable competitive advantage (Lim, Sharkey, & Kim, 1996). Lastly, knowledge of the foreign markets enables the exporting firm to create the most appropriate atmosphere for the relation with its foreign distributors (Styles & Ambler, 1994) and boosts cooperation, information exchange and flexibility in the exporter-foreign distributor relation.…”
Section: Exporter's International Capabilitiesmentioning
confidence: 99%
“…Andersson (2000) argues that the internationalization processes will not start without acting (proactive) individuals and Ibeh and Young (2001) identify the internationalization decision with an entrepreneurial act. CEOs of small and medium-sized enterprises are faced with risk and uncertainty, not only when starting to sell abroad but also when increasing their venture's presence in foreign markets (Lim et al, 1996;Morgan and Katsikeas, 1997). These strategic opportunities are particularly salient in SMEs.…”
Section: Introductionmentioning
confidence: 99%